Effects of calcium infiltration and chitosan coating on storage life and quality characteristics during storage of papaya (Carica papaya L.) - Ali Ahmed Al Eryani, Abdul Raqeeb; Tengku Muda Mohamed, Mahmud; Syed Rastan, Syed Omar; Ab. Rahman, Mohamad Zaki (Academic Journals, 2008)
Mature green stage (Index 2) papaya cv Eksotika II fruits were treated either with 2.5% calcium chloride infiltration, 0.75% chitosan coating, calcium infiltration at 2.5% then subsequently with chitosan coating at 0.75% or untreated fruits as the control. The fruits were then stored at 13±1°C for 35 days. Calcium infiltration was observed to be effective in maintaining the firmness with a slight effect on the weight loss by 2.9 folds and 2.8%, respectively compared to the control. Chitosan coating had less effect on maintaining firmness (2 folds) but gave better effect in preventing weight loss (5.3%). Chitosan coating treatment markedly slowed the ripening of papaya as shown by their retention of weight loss, delayed changes in their external color and other quality aspects. Calcium infiltration and subsequently chitosan coating as a combined treatment further extended the storage life up to 35 days with better retention of fruits firmness and water loss control compared to the treatments mentioned.